Positivism in Philosophical Studies - Maretha, Citra (Journal of Innovation in Teaching and Instructional Media, 2023)
Positivism is a scientific paradigm rooted in empirical philosophy. As a scientific paradigm, positivism has a very broad influence in various fields of science. August Comte was an 18th century French philosopher known as the founder of positivism. In positivism, everything or phenomenon must be able to be measured positively or definitively in order to be measurable. This applies not only to the natural sciences but also to the social sciences. The role of positivist philosophy in the aspect of learning methods can be seen from two things, namely positivist philosophy plays a role in developing learning methods and positivist philosophical thinking plays a role as a learning method. Of course, various learning development activities are based on data and something empirical in nature. About the role of positivist philosophy in relation to learning strategies, which are expressed through the learning method itself. There are several learning methods used today that follow the scientific method, such as discovery learning, project-based learning, and problem-based learning.